Dipping probe electrospray ionization/mass spectrometry for direct on-site and low-invasive food analysis. (15th September 2018) - Usmanov, Dilshadbek T.; Mandal, Mridul K.; Hiraoka, Kenzo; Ninomiya, Satoshi; Wada, Hiroshi; Matsumura, Masaya; Sanada-Morimura, Sachiyo; Nonami, Hiroshi; Yamabe, Shinichi
Highlights: Food analysis by dipping probe electrospray ionization. Low-invasive food analysis with high detection sensitivity. Remote-sampling mass spectrometry. Abstract: Rapid, direct, on-site and noninvasive food analysis is strongly needed for quality control of food. To satisfy this demand, the technique of dipping probe electrospray ionization/mass spectrometry (dPESI/MS) was developed. The sample surface was pricked with a fine acupuncture needle and a sample of ∼200 pL was captured at the needle tip. After drying the sample, the needle tip was dipped into the solvent for ∼50 ms and was moved upward. A high-voltage was applied to the needle to generate electrospray when the needle reached the highest position, and mass spectra were measured with a time-of-flight mass spectrometer. For evaluation of the method, the technique was used to analyze foods such as vegetables, salmon flesh, cow's milk, yogurt, and soy-bean milk. The detected major ions for cow's milk and yogurt were [(Lac)n  + Ca] 2+ with n = 1–6 (where (Lac) is lactose), indicating that Ca 2+ is tightly bound by Lac molecules.